The effect of energy input on the flotation of a platinum ore in a pilot-scale oscillating grid flotation cell. (15th August 2017) - Safari, Mehdi; Harris, Martin; Deglon, David
Graphical abstract: Highlights: The paper investigates the effect of energy input on flotation in a pilot scale OGC. PGM ore were floated at energy input of up to 2.5 W/kg using two bubble sizes. For smaller bubbles, increasing energy input generally decreased the flotation rate. For larger bubbles, increasing energy input generally increased the flotation rate for fine particles. For larger bubbles, increasing energy input leads to an optimum flotation rate for intermediate & coarse particles. Abstract: This study investigates the effect of energy/power input on the flotation of a platinum ore in a pilot-scale oscillating grid flotation cell. Oscillating grids generate near ideal hydrodynamic environments, characterised by turbulence which is relatively homogeneous and isotropic. Secondary rougher feed and primary cleaner tail streams were floated in a pilot-scale oscillating grid flotation cell at power inputs from 0 to 2.5 W/kg, using 0.71 and 1.47 mm bubbles. From this study one may conclude that the effect of energy/power input on the flotation rate is strongly dependent on the particle and bubble size. For large bubbles (1.47 mm), increasing energy input generally leads to an increase in the flotation rate for finer particles (−25 μm) and an optimum flotation rate for intermediate (+25–53 μm) & coarse particles (+53–75 μm). For small bubbles (0.71 mm), increasing energy input leads to a decrease in the flotation rate for all conditions. Optimum conditions for PGM flotation are using small bubbles at low energy inputs, or large bubbles at higher energy inputs.